Women on the Border between Home and Homelessness: Analysing Worker–Client Relationship - Granfelt, Riitta (Social Inclusion, 2021)
Housing First, as implemented in Finland, offers two housing options for people who are homeless or at risk of homelessness. In this context, permanent housing refers to a scattered‐site rental flat or a community‐based housing unit in accordance with the Housing First principle. The focus of our study was on worker-client relationship and its diverse meanings at different stages of women’s housing pathways. Our data consisted of narrative thematic interviews with nine women who lived in scattered housing and three workers of a housing unit. The narratives of the housing unit workers were related to a deep concern for the women who have the most limited choices and who do not always see the housing unit as home. The workers felt frustrated with the inconsistency of care pathways in substance abuse care, psychiatric hospital care as well as gerontological services. Women in scattered housing had received sufficient support at critical stages of their housing pathway from the public service system, which is an integral part of the Finnish Housing First model. In their cases, homelessness and problems with housing had been addressed as part of a holistic effort to improve the quality of their lives either through adult social work, child protection aftercare or psychosocial services. Getting sufficient support in a vulnerable situation in a trust‐based worker-client relationship was a unifying theme of this dataset of women. Our study also challenges the development of services from the perspective of women whose housing pathways are characterised by numerous losses and exclusions, and for whom many services remain out of reach.